Factor structure of the Inventory of Parent Accommodations of Children's Symptoms (IPACS) in a community sample. Issue 3 (2nd July 2016) - Harrison, Lauren E.; Peterson, Catherine C.; Short, Mary B.; Wetterneck, Chad
ABSTRACT: Objective: To examine the factor structure of the Inventory of Parent Accommodations of Children's Symptoms (IPACS) among a community sample of healthy children. Method: An online survey was completed by 220 parents ages 18-65 (M = 34.49; 96% female) for a study examining the effects of parent behaviors on frequency of general sickness and pain complaints (e.g., headaches and stomachaches) in otherwise healthy children. The survey included the IPACS, a measure of parent behaviors and responses to sickness or pain complaints, as well as items that assessed sociodemographics and frequency of sickness and pain complaints in children. Results: Exploratory factors analysis of the IPACS revealed a 12-item measure yielding three discrete, yet related subscales. Additionally, parent accommodations were slightly associated with an increase in sickness and pain complaints in children (r (220) = .153, p<.05). Conclusions: These findings suggest that parent behaviors during general sickness and pain complaints may serve as clinically relevant information that can be used to inform interventions that target specific parent behaviors that might exacerbate symptoms. Future research should examine the convergent validity of this measure with other measures of parenting behavior, as well as the specific utility of the IPACS in chronic illness and pain populations.